1975
DOI: 10.1128/jb.122.1.59-65.1975
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a protein, similar to the sex pilus subunit, in the outer membrane of Escherichia coli cells carrying a derepressed F-like R factor

Abstract: The outer membranes of Escherichia coli K-12 cells carrying a derepressed F-like R factor contain about 7 times 10-4 molecules per cell of a protein similar to the subunit of the sex pili specified by the R factor. This protein pool is absent in cells carrying the repressed variant of the R factor. The size of the pool is about one-half of the amount of protein incorporated into mature sex pili at the peak of production and is independent of the phase of growth of the culture. The molecular weight of the prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1975
1975
1984
1984

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…This is an extension of the observation reported by Brinton (9) that disruption of the mucopeptide layer by penicillin treatment has no effect on sex pilus production. This observation, taken in conjunction with other work which has shown that disruption of the lipopolysaccharide results in reduced recipient ability (18,22) and donor ability (Bishop and Beard, manuscript in preparation) in conjugating cells, suggests that the outer membrane (also the location of the pool of sex pilus subunits [3 ]) is the important region of the cell envelope upon which attention should fall during investigations into the precise nature of the "conjugation bridge" (10,11). Second, we have shown that surface exclusion, mediated by at least one gene on the excluding plasmid (traS) (23), is totally abolished by disruption of the mucopeptide layer in the donor cell.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…This is an extension of the observation reported by Brinton (9) that disruption of the mucopeptide layer by penicillin treatment has no effect on sex pilus production. This observation, taken in conjunction with other work which has shown that disruption of the lipopolysaccharide results in reduced recipient ability (18,22) and donor ability (Bishop and Beard, manuscript in preparation) in conjugating cells, suggests that the outer membrane (also the location of the pool of sex pilus subunits [3 ]) is the important region of the cell envelope upon which attention should fall during investigations into the precise nature of the "conjugation bridge" (10,11). Second, we have shown that surface exclusion, mediated by at least one gene on the excluding plasmid (traS) (23), is totally abolished by disruption of the mucopeptide layer in the donor cell.…”
Section: Resultssupporting
confidence: 75%
“…Bacterial strains and R factors. Bacterial strains UB1005 and UB1025, and R factors Rldrdl9.Kl and Rldrdl9.K-1 (derivatives of Rldrdl9 that carry mutually exclusive resistance determinants), have been described previously (3).…”
Section: Methodsmentioning
confidence: 99%
“…Our observations indicate that it only takes 10 s for a pilus to disappear (retract) at 500C, and it is possible that they retract as fast in the presence of cyanide (13). The pilus might dissociate into subunits (pilin) as it retracts (11), and these subunits might enter the pool of pilin that is probably located in the outer membrane (1,14). The dissociation of a pilus at its base in the membrane could be spontaneous, or it might require an enzyme.…”
Section: Discussionmentioning
confidence: 80%
“…Rldrd-19, which only mediates resistance to kanamycin (4). From the EcoRI digest pattem it was shown that many fragments have been deleted, and on comparing the pattern with the map of plasmid Rldrd-19 (7) it is clear that the deletion covers all of the r-determinant except for the fragments F (the kanamycin resistance fragment) and J (Fig.…”
Section: Resultsmentioning
confidence: 95%